Outside : activating cloth to enhance the way we live - Macbeth, Penny; Barber, Claire (Cambridge Scholars Publishing, 2014)
Outside: Activating Cloth to Enhance the Way We Live explores cloth's value, relevance and impact on societies today, recognising the constantly evolving fields of expression, often sited beyond art mediated contexts. The book explores cloth's potential as a metaphor for consciousness, a carrier of narrative, and a catalyst for community empathy and cohesion. Invited curators, philosophers, artists and scholars employ a variety of didactic styles that include the conversational, metaphoric ...